2016
DOI: 10.1103/physrevlett.117.245501
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of a Parent {130}310α Martensitic Twinning

Abstract: In bcc metastable β titanium alloys, and particularly in superelastic alloys, a unique {332}⟨113⟩ twinning system occurs during plastic deformation. However, in situ synchrotron x-ray diffraction during a tensile test shows that the β phase totally transforms into α^{''} martensite under stress in a Ti-27Nb (at. %) alloy. {332}⟨113⟩_{β} twins are thus not formed directly in the β phase but are the result of the reversion of {130}⟨310⟩_{α^{''}} parent twins occurring in martensite under stress. The formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 40 publications
13
62
1
Order By: Relevance
“…Depending on different historical processes, the particle morphologies of ω phase can be ellipsoidal or cuboidal after ageing [10][11][12] and plate-like in strained titanium alloys [13][14][15]. These morphological differences for ω phase can be attributed to both compositional partition and stressing condition [10][11][12][16][17][18]. However, the model of collapsing one pair of {1 1 1} β planes to an intermediate position leaving the adjacent {1 1 1} β planes unaltered were proved and widely accepted as the formation mechanism of ω phase for nearly all cases [3,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on different historical processes, the particle morphologies of ω phase can be ellipsoidal or cuboidal after ageing [10][11][12] and plate-like in strained titanium alloys [13][14][15]. These morphological differences for ω phase can be attributed to both compositional partition and stressing condition [10][11][12][16][17][18]. However, the model of collapsing one pair of {1 1 1} β planes to an intermediate position leaving the adjacent {1 1 1} β planes unaltered were proved and widely accepted as the formation mechanism of ω phase for nearly all cases [3,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the model of collapsing one pair of {1 1 1} β planes to an intermediate position leaving the adjacent {1 1 1} β planes unaltered were proved and widely accepted as the formation mechanism of ω phase for nearly all cases [3,19,20]. Amongst them, thin layer ω phase located along the twin boundary, which was called ITB-ω [18], deserves more investigation. The two twinning systems observed in β-type Ti alloys are {1 1 2} <1 1 1> β [18,19,[21][22][23][24][25] and {3 3 2} <1 1 3> β [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…35,36) Recently, Gloriant et al 37) and Tsuchiya et al 38) have reported tensile deformation behavior of TiNb and TiMo alloys, respectively, focusing on the formation of {332}©113ª deformation twins. Similarly, Raabe et al 39) and Gloriant et al 40) have studied formation mechanism of the {332}©113ª twins in TiNb alloys. Tobe et al 41) have reported possible twinning modes in metastable ¢-type Ti alloys based on the theory of the crystallography of deformation twinning.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of these twinning modes strongly depends on the lattice parameters of β and αʺ martensite [19,28]. For instance, Inamura et al [19] reported the activation of different twinning modes in Ti- (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)Nb-3Al (wt.%) alloys, namely {111} α"type I, <211> αʺ -type II and {011} αʺ -compound twinning, which is associated with Nb content.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a better understanding of deformation mechanisms of αʺ martensite is essential for the development of high-performance alloys [6,[31][32][33]. So far, few studies have analyzed deformation behaviors of αʺ martensite in β-Ti alloys [25,34,35]. These studies have reported {130} αʺ -compound twinning in a Ti-25Ta-20Nb (wt.%) alloy [25], and {130} αʺ -compound and {103} αʺ -compound twinning in a Ti-42Nb (wt.%) alloy [34].…”
Section: Introductionmentioning
confidence: 99%